2011
DOI: 10.2174/1876817201103010045
|View full text |Cite
|
Sign up to set email alerts
|

Malignant Phyllodes Tumor of the Breast: A Case Report

Abstract: Phyllodes tumors of the breast have biphasic histological features with both epithelial and stromal components. Careful characterization of the stromal compartment is critical since it is the pathologic features of the stromal cells that determine its malignant potential. We present a case report of a woman with an aggressive malignant phyllodes tumor with sarcomatous differentiation, who succumbed to metastatic disease within 8 months of initial presentation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…This is the second case reported in Kermanshah, Iran. [1] Malignant PT represents less than 1% of all breast malignancies and commonly has an indolent clinical course with a propensity for local recurrence [9]. Abusalem et al [10] reported that in their study, the mean age of patients with borderline PT was 42 years and higher than benign (37 years) and malignant (41 years) Ts.…”
Section: Discussionmentioning
confidence: 99%
“…This is the second case reported in Kermanshah, Iran. [1] Malignant PT represents less than 1% of all breast malignancies and commonly has an indolent clinical course with a propensity for local recurrence [9]. Abusalem et al [10] reported that in their study, the mean age of patients with borderline PT was 42 years and higher than benign (37 years) and malignant (41 years) Ts.…”
Section: Discussionmentioning
confidence: 99%
“…Giant MPTB can lead to the development of hypoglycemia, which results from increased insulin-like growth factor 2 levels produced by the tumor ( 15 , 16 ). Metastasis from MPTB occurs in 6.2–25% of cases ( 17 ), most frequently metastasizing to the lung, bone and liver ( 18 , 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…[2] Approximately 16% to 30% of phyllodes tumors are malignant [3] ; while difficult to identify, they are generally characterized by rapidly growing huge masses that may present with delayed metastases, mainly to the lung. [4] Surgery with sufficient resection margins is the standard treatment for phyllodes tumors, and adjuvant radiotherapy is recommended to reduce local recurrence. Adjuvant chemotherapy is suggested for selected patients with large, high risk, or recurrent tumors only after thorough evaluation.…”
Section: Introductionmentioning
confidence: 99%